Residual Shear Strength and Other Geotechnical Properties of Clay Mixed with Different Sand Ratios - Abdulnafaa, Mohammed D.; Alshuwaykhi, Abdulnasser Y.; Al-Dabbagh, Aymen W. (Engineering, Technology & Applied Science Research, 2025)
The current research investigates the residual shear strength of clay soils to which different percentages (5, 10, 15, and 20%) of sand are added, playing a pivotal role in determining the stability of steep slopes on these soils. The residual shear strength was compared with the shear strength calculated from the direct shear test and the unconfined compression strength test. According to the results, the clay soil’s swelling ranged from medium to high, and its engineering characteristics were similar to that of all clay soils found in most sloped areas and hills in Mosul city. Also, a notable reduction was observed in the plasticity index with an increase in the sand percentage. In the residual shear test, a rise in shear coefficients (effective angle of internal friction (Φ’) and cohesion(c’)) was demonstrated with an increase in the percentage of sand addition up to a certain limit (15%), which is the same percentage that gave values for (c and Φ) in the direct shear test.